2012
DOI: 10.3168/jds.2012-5412
|View full text |Cite
|
Sign up to set email alerts
|

Use of algae or algal oil rich in n-3 fatty acids as a feed supplement for dairy cattle

Abstract: Fish oil is used as a ration additive to provide n-3 fatty acids to dairy cows. Fish do not synthesize n-3 fatty acids; they must consume microscopic algae or other algae-consuming fish. New technology allows for the production of algal biomass for use as a ration supplement for dairy cattle. Lipid encapsulation of the algal biomass protects n-3 fatty acids from biohydrogenation in the rumen and allows them to be available for absorption and utilization in the small intestine. Our objective was to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
66
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 32 publications
20
66
1
3
Order By: Relevance
“…This result is in agreement with Stamey et al (2012) who found no detrimental influence on milk yield or milk fat yield in Holstein cows receiving rumen protected algal biomass or rumen protected algal oil. In the present study the form of algae supplementation was protected similarly to that used by Stamey et al (2012).…”
Section: Milk Production and Fatty Acid Compositionsupporting
confidence: 82%
See 4 more Smart Citations
“…This result is in agreement with Stamey et al (2012) who found no detrimental influence on milk yield or milk fat yield in Holstein cows receiving rumen protected algal biomass or rumen protected algal oil. In the present study the form of algae supplementation was protected similarly to that used by Stamey et al (2012).…”
Section: Milk Production and Fatty Acid Compositionsupporting
confidence: 82%
“…This result is in agreement with Stamey et al (2012) who found no detrimental influence on milk yield or milk fat yield in Holstein cows receiving rumen protected algal biomass or rumen protected algal oil. In the present study the form of algae supplementation was protected similarly to that used by Stamey et al (2012). Similarly, Moate et al (2013), offering different amounts of algal meal to lactating cows, found no alterations on milk yield although milk fat yield decreased with the addition of DHA.…”
Section: Milk Production and Fatty Acid Compositionsupporting
confidence: 82%
See 3 more Smart Citations